2020
DOI: 10.36834/cmej.69328
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between regional medical campus enrollment and rates of matching to family medicine residency

Abstract: Background: The Michael G. DeGroote School of Medicine expanded its medical education across three campus sites (Hamilton, Niagara Regional and Waterloo Regional) in 2007. Ensuring the efficacy and equivalency of the quality of training are important accreditation considerations in distributed medical education.  In addition, given the social accountability mission implicit to distributed medical education, the proportion of learners at each campus that match to family medicine residency programs upon graduati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…12 Medical schools may be interested in Bakker and colleagues' study: "The relationship between regional medical campus enrollment and rates of matching to family medicine residency" which points to contextual differences between regional and main medical school campuses and then subsequently affect PG training choices. 13 We are also very pleased to see Gallinger and colleagues report: ""CaRMS at 50: Making the match for medical education" which examines the evolution of the application and matching system over the past half century, and CaRMS' role in the process. They concluded that the system needs to evolve with future needs without compromising its current advantages.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…12 Medical schools may be interested in Bakker and colleagues' study: "The relationship between regional medical campus enrollment and rates of matching to family medicine residency" which points to contextual differences between regional and main medical school campuses and then subsequently affect PG training choices. 13 We are also very pleased to see Gallinger and colleagues report: ""CaRMS at 50: Making the match for medical education" which examines the evolution of the application and matching system over the past half century, and CaRMS' role in the process. They concluded that the system needs to evolve with future needs without compromising its current advantages.…”
mentioning
confidence: 99%
“…Medical schools may be interested in Bakker and colleagues’ study: “The relationship between regional medical campus enrollment and rates of matching to family medicine residency” which points to contextual differences between regional and main medical school campuses and then subsequently affect PG training choices. 13 …”
mentioning
confidence: 99%